The Impact of Training and Support Satisfaction on Employment Outcomes: A Case Study of the Global Skills Training Program 2024 in South Sumatra Province, Indonesia - Fajarsyah, Reza; Okfernando, Raphel (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This research examines the relationship between training satisfaction, support satisfaction, and employment outcomes in the Global Skills Training Program 2024 in South Sumatra, Indonesia. Training satisfaction refers to participants' evaluations of the content, delivery methods, and instructor effectiveness, while support satisfaction reflects their perceptions of career counseling, job placement services, and institutional support. A quantitative approach was employed, analyzing survey data from 240 participants. Statistical analyses using Jamovi Software included a two-sample t-test for gender-based differences, one-way ANOVA for age group comparisons, and logistic regression to examine the impact of satisfaction levels on employment status. Key findings indicate that training satisfaction significantly improves employment transitions, whereas support satisfaction plays a crucial role in reducing unemployment and self-employment rates. Male participants reported higher support satisfaction than female participants, while age differences were not significant. These results highlight the need for personalized training content, robust post-training support, and equitable access to career resources to enhance employability. From a policy perspective, this study underscores the importance of integrating career counseling, job placement services, and mentorship programs into vocational training initiatives. Training providers should focus on reducing gender disparities in support services and enhancing engagement strategies to ensure effective workforce transitions. These findings contribute to the broader discourse on workforce development and offer evidence-based recommendations to align skills training with labor market needs.